National Income Estimates in the Statistical Policy of an Underdeveloped Area: A Further Comment - Stewart, Ian G. (Review of Economic Studies, 1954)
Journal Article National Income Estimates in the Statistical Policy of an Underdeveloped Area: A Further Comment Get access Ian G. Stewart Ian G. Stewart Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 3, 1954, Pages 226–227, https://doi.org/10.2307/2295880 Published: 01 January 1954